A alienação do jovem Hegel - Zandoná, Felipe Biavati (Universidade do Vale do Rio dos Sinos, 2021)
This dissertation investigates the bases of the phenomenon of alienation in the so-called Hegel’s early theological writings. The research method used is that of bibliographic review, by reading the writings The Positivism of the Christian Religion and The Spirit of Christianity and its Fate, in addition to other works related to the central theme of the research. The work begins the study of the terms Entäusserung and Entfremdung, understanding and differentiation are fundamental for understanding the phenomenon of alienation. From this, the research will bring an explanation about the time and how influences that determined Hegel's thought in his youth, and how a criticism directed at positive religion develop and became a central theme of his philosophy at this time. Given the context presented, the relations between positive religion, morality, and alienation are analyzed from the concepts of strangeness, division, self-deception, and disenchantment, and how the alienating phenomenon goes beyond the purely religious and factor sphere, influences the institutional functioning of civil society. As a conclusion, from the analysis carried out, it is possible to identify positive religion as a basis for the phenomenon of alienation based on the criticism directed by the young Hegel, especially Christianity, when it imposes a supposed moral truth to the detriment of the subjectivities that make up the total ethics of life.
Keywords: Jovem Hegel; Religião positiva; Alienação; Moral; Young Hegel; Positive religion; Alienation; Moral; ACCNPQ::Ciências Humanas::Filosofia